The Identification And Management Of Major Risks In The Malaysian Construction Industry - Cheng , Siew Goh; Rahman, Hamzah Abdul (Penerbit Universiti Sains Malaysia, 2013)
Effective risk management can bring greater rewards to project performance by enhancing productivity. The objectives of this study are to identify the major risks associated with the Malaysian construction industry and to evaluate the practical measures that the various local construction industry players would take to respond to those risks. A mixed method of questionnaire and interviews was used to investigate the current trend of risk management implementation in the Malaysian construction industry. Financial risk and time risk are found to be the major risks in terms of the occurrence frequency and the impacts. A lack of knowledge and the associated costs of risk management application are the main reasons given by local contractors who lag behind in implementing risk management in their practices. It can be deduced that risk management is still at an early stage of development in the Malaysian construction industry